The naturalistic reinforcement of worry from positive and negative emotional contrasts: Results from a momentary assessment study within social interactions. (December 2022) - Newman, Michelle G.; Schwob, Jeremy T.; Rackoff, Gavin N.; Doren, Natalia Van; Shin, Ki Eun; Kim, Hanjoo
Abstract: Background: The Contrast Avoidance Model (Newman & Llera, 2011) proposes that worry is reinforced by avoiding a negative contrast and increasing the likelihood of a positive contrast. Objective: To determine if reinforcement of worry occurs naturalistically via contrasts in both negative and positive emotion. Method: Using event-contingent momentary assessment we assessed social interactions, pre-interaction state worry and pre-post interaction positive and negative emotion. Participants with generalized anxiety disorder (GAD; N = 83) completed an online questionnaire after social interactions lasting at least 1 min for 8 days. Three-level multilevel models were conducted. Results: Higher worry was concurrently associated with increased negative emotion and decreased positive emotion. Regardless of pre-interaction worry level, negative emotion decreased, and positive emotion increased from before to after interactions, suggesting that most interactions were benign or positive. At lower levels of pre-interaction worry, participants experienced increased negative emotion and decreased positive emotion from before to after interactions. At higher levels of pre-interaction worry, participants experienced decreased negative emotion and increased positive emotion from before to after interactions. Conclusion: Among persons with GAD, worrying before social interactions may be both negatively and positively reinforced; furthermore, not worrying before social interactions may be both negatively and positively punished. Highlights: Tested contrast avoidance theory regarding negative and positive affect. Used event-contingent momentary assessment of social interactions. Worry led to concurrently high negative affect and low positive affect. Worry before social interactions was positively and negatively reinforced. Not worrying before social interactions was positively and negatively punished.